The Serum MicroRNA Signatures for Pancreatic Cancer Detection and Operability Evaluation - Yan, Qiuliang; Hu, Dandan; Li, Maolan; Chen, Yan; Wu, Xiangsong; Ye, Qinghuang; Wang, Zhijiang; He, Lingzhe; Zhu, Jinhui (Frontiers in Bioengineering and Biotechnology, 2020)
Pancreatic cancer (PC) has high morbidity and mortality and is considered to be the fourth leading cause of cancer death. Its diagnosis and treatment are difficult. Liquid biopsy makes early diagnosis of pancreatic cancer possible. We expression profiles of 2,555 serum miRNAs in 100 pancreatic cancer patients and 150 healthy controls. With advanced feature selection methods, we identified 13 pancreatic cancer signature miRNAs that can classify the pancreatic cancer patients and healthy controls. For pancreatic cancer treatment, operation is still the first choice. But many pancreatic cancer patients are already inoperable. Therefore, we compared the 79 inoperable and 21 operable patients and identified 432 miRNAs that can predict whether a pancreatic cancer patient was operable. The functional analysis of the 13 pancreatic cancer signatures and the 432 operability miRNAs revealed the molecular mechanisms of pancreatic cancer and shield light on the diagnosis and therapy of pancreatic cancer in clinical practice.